Toward 3D dose verification of an electronic brachytherapy source with a plastic scintillation detector. Issue 5 (3rd March 2022) - Georgi, Peter; Kertzscher, Gustavo; Nyvang, Lars; Šolc, Jaroslav; Schneider, Thorsten; Tanderup, Kari; Johansen, Jacob Graversen
Abstract: Background: Electronic brachytherapy (eBT) is considered a safe treatment with good outcomes. However, eBT lacks standardized and independent dose verification, which could impede future use. Purpose: To validate the 3D dose‐to‐water distribution of an electronic brachytherapy (eBT) source using a small‐volume plastic scintillation detector (PSD). Methods: The relative dose distribution of a Papillon 50 (P50) (Ariane Medical Systems, UK) eBT source was measured in water with a PSD consisting of a cylindrical scintillating BCF‐12 fiber (length: 0.5 mm, Ø: 1 mm) coupled to a photodetector via an optical fiber. The measurements were performed with the PSD mounted on a motorized stage in a water phantom (MP3) (PTW, Germany). This allowed the sensitive volume of the PSD to be moved to predetermined positions relative to the P50 applicator, which pointed vertically downward while just breaching the water surface. The percentage depth‐dose (PDD) was measured from 0 to 50 mm source‐to‐detector distance (SDD) in 1–3 mm steps. Dose profiles were measured along two perpendicular axes at five different SDDs with step sizes down to 0.5 mm. Characterization of the PSD consisted of determining the energy correction through Monte Carlo (MC) simulation and by measuring the stability and dose rate linearity using a well‐type ionization chamber as a reference. The measured PDD and profiles were validated with corresponding MC simulations. Results: The measured and simulated PDD curves agreed within 2% (except at 0 mm and 43 mm depth) after the PSD measurements were corrected for energy dependency. The absorbed dose decreased by a factor of 2 at 7 mm depth and by a factor of 10 at 26 mm depth. The measured dose profiles showed dose gradients at the profile edges of more than 50%/mm at 5 mm depth and 15%/mm at 50 mm depth. The measured profile widths increased 0.66 mm per 1 mm depth, while the simulated profile widths increased 0.74 mm per 1 mm depth. An azimuthal dependency of > 10% was observed in the dose at 10 mm distance from the beam center. The total uncertainty of the measured relative dose is < 2.5% with a positional uncertainty of 0.4 mm. The measurements for a full 3D dose characterization (PDD and profiles) can be carried out within 8 h, the limiting factor being cooling of the P50. Conclusion: The PSD and MP3 water phantoms provided a method to independently verify the relative 3D dose distribution in water of an eBT source.